Central composite design approach towards optimization of flamboyant pods derived steam activated carbon for its use as heterogeneous catalyst in transesterification of Hevea brasiliensis oil. (August 2015) - Dhawane, Sumit H.; Kumar, Tarkeshwar; Halder, Gopinath
Graphical abstract: Highlights: Activated carbon was prepared from novel precursor flamboyant pods ( Delonix regia ). Activation process was optimized using central composite design approach. Prepared activated carbon at optimized condition was used as support for KOH. Carbon based heterogeneous catalyst was used in transesterification of HBO. Effect of catalyst loading and alcohol ratio on biodiesel yield was studied. Abstract: The present investigation emphasises the preparation of carbon based KOH impregnated heterogeneous catalyst from flamboyant pods ( Delonix regia ) for the production of biodiesel from novel feedstock Hevea brasiliensis oil (HBO). Initially, carbonized char was physically activated by superheated steam and the process was optimized to study the effects of activation time and temperature by central composite design approach (CCD) using response surface methodology (RSM). Activated carbon was impregnated with KOH at four different ratios. Biodiesel production process was carried out at constant temperature 60 °C, reaction time 1 h, and 5 g of carbon based catalyst at varying quantities of catalyst loading (0.5, 2, 3.5, 5 wt%) and methanol to oil ratio (5:1–20:1). The influence of parameters on the biodiesel yield at varied condition was studied. Maximum yield of 89.3% was obtained at methanol to oil ratio 15:1 and catalyst loading 3.5 wt% and corresponding yield at same process parameters was observed to be 88.7% implying the significant activity of catalyst in reutilization. Produced biodiesel was characterized following ASTM standards. The experimental analysis confirmed that the carbonaceous catalyst developed from flamboyant pods under optimized condition is capable of transesterifying HBO into biodiesel.